2016
DOI: 10.1093/jxb/erw352
|View full text |Cite
|
Sign up to set email alerts
|

Axillary buds are dwarfed shoots that tightly regulate GA pathway and GA-inducible 1,3-β-glucanase genes during branching in hybrid aspen

Abstract: HighlightAxillary buds uniquely regulate gibberellin (GA) pathway genes, enabling them to stay inhibited but simultaneously poised for growth. Decapitation promotes expression of GA-inducible 1,3-β-glucanase genes that function to reinvigorate symplasmic connections to the stem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 104 publications
(192 reference statements)
1
43
0
Order By: Relevance
“…In O. sativa, GH17 is the largest GH family [17]. In A. thaliana and Populus trichocarpa, it comprises 50 and 100 members, respectively [54]. The GH3 family includes β-1,3-glucanase (glucan endo-1,3-β-D-glucosidase, E.C 3.2.1.39), glucan 1,3-β-glucosidase (E.C 3.2.1.58), licheninase (EC 3.2.1.73), glucan 1,4-β-glucosidase (EC 3.2.1.74) activities (enzyme.expasy.org/).…”
Section: Gh 17mentioning
confidence: 99%
“…In O. sativa, GH17 is the largest GH family [17]. In A. thaliana and Populus trichocarpa, it comprises 50 and 100 members, respectively [54]. The GH3 family includes β-1,3-glucanase (glucan endo-1,3-β-D-glucosidase, E.C 3.2.1.39), glucan 1,3-β-glucosidase (E.C 3.2.1.58), licheninase (EC 3.2.1.73), glucan 1,4-β-glucosidase (EC 3.2.1.74) activities (enzyme.expasy.org/).…”
Section: Gh 17mentioning
confidence: 99%
“…In that regard, some xylem‐specific components of the wall biosynthesis/remodeling machinery are regulated by the SL pathway. For example, in hybrid aspen, a SL‐dependent up‐regulation of 1,3‐β‐glucanases (GH17 family, α‐clade) controls shoot elongation via callose hydrolysis at sieve plates and plasmodesmata (Rinne, Paul, Vahala, Kangasjärvi, & van der Schoot, ). In addition, SL have been suggested as positive regulators of cambium activity in Arabidopsis , pea and in the woody plant Eucalyptus globulus .…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported that in perennial trees the release of bud dormancy requires the removal of callose in the plamodesmata in order to restore the symplastic connectivity in the meristem (Rinne et al 2011;Rinne et al 2001;Rinne et al 2016). Although we saw there is a vascular connection between the buds and the mother bulb, it is plausible to think that it might not be very functional when callose is not entirely removed from plasmodesmata in dormant buds, and therefore less carbon resources can be remobilized into those buds.…”
Section: Dormancy and Sink Strength In Tulip Axillary Budsmentioning
confidence: 99%
“…Apical dominance is the control of the apex of the plant over the outgrowth of the axillary buds (Cline 1994). Axillary buds repressed by apical dominance are also called para-dormant and they resume growth upon decapitation of the apex (Rinne et al 2016). Evidence from apical dominance studies indicates that the auxin produced in the apex of the plant (Cline 1996;Cline 2000;Cline et al 2001;Domagalska and Leyser 2011) and the high sugar demand of the apex (Mason et al 2014;Barbier et al 2015) and hence, a kind of starvation of the axillary buds, are the initial inhibitory effectors in axillary bud outgrowth.…”
Section: Introductionmentioning
confidence: 99%